2007
DOI: 10.1143/jjap.46.4921
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Cantilever-Type Ultrasonic Motor Using Pb-Free Multilayer Piezoelectric Ceramics

Abstract: A Miniature cantilever-type ultrasonic motor was fabricated using multilayer piezoelectric ceramics (MLPC) made of (Sr,Ca)2NaNb5O15 (SCNN), a Pb-free piezoelectric material, and the electrical driving properties were investigated. The displacement of SCNN-MLPC was 177 nm at 100 V, which was 10-fold the voltage of MLPC made of Pb(Zr,Ti)O3–Pb(Ni,Nb)O3–Pb(Zn,Nb)O3 (PZT). The ultrasonic motor using SCNN-MLPC started to rotate at 3.8 Vp–p, and showed the following characteristics: a revolution speed of Ω0=517 rpm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…These materials can be co-sintered with cost-effective nickel electrodes [7], which is not currently achievable for PZT [8]. Tou et al [9] laid the groundwork for hard bismuth-based piezoceramics to be used in ultrasonic cleaners, and Doshida et al [10,11] demonstrated that lead-free piezoceramics have better performance than PZT for high power applications. Recently, a BaTiO 3 (BT)-based solid solution, (1 − x)Ba(Zr 0.2 Ti 0.8 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 (BZT-xBCT), has attracted considerable attention due to its promising small and large signal piezoelectric properties [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be co-sintered with cost-effective nickel electrodes [7], which is not currently achievable for PZT [8]. Tou et al [9] laid the groundwork for hard bismuth-based piezoceramics to be used in ultrasonic cleaners, and Doshida et al [10,11] demonstrated that lead-free piezoceramics have better performance than PZT for high power applications. Recently, a BaTiO 3 (BT)-based solid solution, (1 − x)Ba(Zr 0.2 Ti 0.8 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 (BZT-xBCT), has attracted considerable attention due to its promising small and large signal piezoelectric properties [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These devices were mainly composed of PZT-based piezoelectric ceramics with a high mechanical quality factor Q m , which is called hard PZT. However, the resonant vibration of [47,72,73].…”
Section: +mentioning
confidence: 99%
“…Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor PZT ceramics contain a large amount of Pb; therefore, lead-free piezoelectric materials to replace PZT are becoming increasingly required from the viewpoint of environmental protection. As materials for lead-free high-power applications, SrBi 2 Nb 2 O 9 and (Sr,Ca) 2 NaNb 5 O 15 ceramics and LiNbO 3 single crystals have been reported [2][3][4][5][6][7]. However, there have been few studies on the high-power piezoelectric characteristics of lead-free…”
Section: Please Scroll Down For Articlementioning
confidence: 99%